Mechanism of PGC-1α-mediated mitochondrial biogenesis in cerebral ischemia–reperfusion injury - Yuan, Ying; Tian, Yuan; Jiang, Hui; Cai, Luo-yang; Song, Jie; Peng, Rui; Zhang, Xiao-ming (Frontiers in Molecular Neuroscience, 2023)
Cerebral ischemia-reperfusion injury (CIRI) is a series of cascade reactions that occur after blood flow recanalization in the ischemic zone in patients with cerebral infarction, causing an imbalance in intracellular homeostasis through multiple pathologies such as increased oxygen free radicals, inflammatory response, calcium overload, and impaired energy metabolism, leading to mitochondrial dysfunction and ultimately apoptosis. Rescue of reversibly damaged neurons in the ischemic hemispheric zone is the key to saving brain infarction and reducing neurological deficits. Complex and active neurological functions are highly dependent on an adequate energy supply from mitochondria. Mitochondrial biogenesis (MB), a process that generates new functional mitochondria and restores normal mitochondrial function by replacing damaged mitochondria, is a major mechanism for maintaining intra-mitochondrial homeostasis and is involved in mitochondrial quality control to ameliorate mitochondrial dysfunction and thus protects against CIRI. The main regulator of MB is peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α), which improves mitochondrial function to protect against CIRI by activating its downstream nuclear respiratory factor 1 (NRF1) and mitochondrial transcription factor A (TFAM) to promote mitochondrial genome replication and transcription. This paper provides a theoretical reference for the treatment of neurological impairment caused by CIRI by discussing the mechanisms of mitochondrial biogenesis during cerebral ischemia-reperfusion injury.